2022
DOI: 10.1021/acsanm.2c01396
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed VO2 Nanoparticle/Polymer Composite Films for Thermochromic Applications

Abstract: Thin films composed of vanadium dioxide (VO2), a well-known thermochromic material with reversible insulator-to-metal-transition near room temperature, are intriguing for intelligent and energy-efficient heat-blocking applications. However, the conventional vacuum-based deposition methods often involve a high-temperature annealing process, and oxidation of VO2 under air exposure further limits their practical applications. In this work, we demonstrate a room-temperature solution process to prepare VO2-based th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…In the sector of smart windows, a comparison between various thermochromic materials is pivotal, especially concerning their energy-saving potential. Among these materials, vanadium dioxide (VO 2 ) coatings have garnered attention due to their cost-effectiveness and scalability for large-scale applications [ 193 ]. For instance, Louloudakis et al [ 176 , 194 ] has demonstrated that VO 2 coatings exhibit a notable thermochromic transition at low temperature, shifting from a transparent to a reflective state upon heating.…”
Section: Application In Heat Detection Systemsmentioning
confidence: 99%
“…In the sector of smart windows, a comparison between various thermochromic materials is pivotal, especially concerning their energy-saving potential. Among these materials, vanadium dioxide (VO 2 ) coatings have garnered attention due to their cost-effectiveness and scalability for large-scale applications [ 193 ]. For instance, Louloudakis et al [ 176 , 194 ] has demonstrated that VO 2 coatings exhibit a notable thermochromic transition at low temperature, shifting from a transparent to a reflective state upon heating.…”
Section: Application In Heat Detection Systemsmentioning
confidence: 99%